Chemical composition of essential oil of Machilus Japonica Siebold & Zucc. (Lauraceae) from Vietnam - Khien, Pham Van; Huy, Do Quang; Huong, Do Thi Viet (VNU Journal of Science: Natural Sciences and Technology; Vol 25 No 2, 2009)
Abstract